Diastase Enzyme Activity as a Quality and Clinical Safety Parameter of Pure Honey in Pharmacies in the Pasar Kemis - Zakka, Gulsyaniraz Qadhi; Hayatun Nufus (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2026)
Diastase enzyme is a natural constituent of honey highly sensitive to heat and storage, making its activity a primary indicator for bio-integrity and authenticity. This study aims to evaluate diastase activity in pure honey at pharmacies to ensure compliance with quality standards and consumer safety. This laboratory experimental study was conducted in Pasar Kemis and the Pharmaceutical Chemistry Laboratory of Universitas Indonesia Maju. The population included all packaged pure honey in pharmacies, using purposive sampling for five brands (samples A, B, C, D, and E). Instruments used included a spectrophotometer at 660 nanometers, with simple linear regression to determine the Diastase Number. Analysis revealed significant differences in enzymatic activity between samples. Sample A demonstrated optimal quality (7.49 DN), while samples B (0.12 DN), C (0.15 DN), and D (2.53 DN) were far below the minimum threshold of 3 units as per Indonesian National Standard 8664:2024. This decrease reflects molecular protein denaturation that is visually undetectable but implies therapeutic loss and toxic degradation risk. There is a significant anomaly between marketing authorization legality and biological quality in retail, necessitating systemic strengthening of post-market surveillance by regulatory authorities.